1988
DOI: 10.1530/acta.0.1180483
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the catecholamine content of the rat brain: effects of neonatal castration and androgenization

Abstract: The long-term organizational influence of perinatal androgen manipulations upon the central noradrenergic and dopaminergic systems was investigated in the rat. Males were castrated or sham-operated upon within 24 h of birth. Newborn females received either five daily sc injections of 100 \g=m\g of testosterone in oil, or vehicle only. Groups of animals were then decapitated at ages ranging from 12 to 180 days. Levels of noradrenaline and dopamine were measured in six brain regions using high-performance liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Nei ther juvenile gonadectomy nor early exposure to testos terone propionate significantly affected the observed changes in NE utilization in the hypothalamus or cortex. Therefore, while there have been reports indicating that neonatal gonadal hormones influence development in hypothalamic NE projections [ 10], and that gonadal hor mones establish sexual dimorphism in monoaminergic cells [8], pubertal secretion of gonadal androgens does not appear to account for the changes in hypothalamic NE utilization that we observed over adolescent develop ment in male rats. Thus, changes in function of cate cholamine neurons during this developmental period oc curs independent of changes in gonadal hormones.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Nei ther juvenile gonadectomy nor early exposure to testos terone propionate significantly affected the observed changes in NE utilization in the hypothalamus or cortex. Therefore, while there have been reports indicating that neonatal gonadal hormones influence development in hypothalamic NE projections [ 10], and that gonadal hor mones establish sexual dimorphism in monoaminergic cells [8], pubertal secretion of gonadal androgens does not appear to account for the changes in hypothalamic NE utilization that we observed over adolescent develop ment in male rats. Thus, changes in function of cate cholamine neurons during this developmental period oc curs independent of changes in gonadal hormones.…”
Section: Discussioncontrasting
confidence: 79%
“…Thus, we hypothesized that pubertal changes in gonadal function might underlie the changes in hypothalamic NE turnover that take place from a late juvenile age to young adulthood. Neonatal sex hormones have been reported to influence the devel opment of NE levels in the hypothalamus while not alter ing the development of NE levels in the cerebral cortex, midbrain, or cerebellum [10], Contrary evidence that neonatal castrations in male rats do not significantly af fect catecholamine levels in the hypothalamus, however, has also been reported [11].…”
Section: Introductionmentioning
confidence: 97%
“…taner et al, 1987). Biochemical studies in juvenile rats have further shown that, whereas prenatal hormone manipulations can affect the time course of expected developmental changes in cortical NA levels (Stewart and Rajabi, 1994), manipulations performed only a few days later on the day of birth are without significant effect (Siddiqui and Gilmore, 1988;Stewart et al, 1991;Siddiqui and Shah, 1997). Taken together, these studies suggest that cortical NA afferents may be subject to a critical period of hormone sensitivity that is confined to prenatal life, and that from earliest postnatal periods onward these afferents are largely resilient to changes in the hormonal milieu.…”
Section: Hormone Insensitivity Of Cortical Noradrenalinmentioning
confidence: 99%
“…Other authors [6,22] reported no significant differences between hypothalamic CA levels at day 2 or 12 after birth. We observed significantly higher hypo thalamic NA levels in males on postnatal day 10.…”
Section: Discussionmentioning
confidence: 92%